Enlightenment’s and Humanistic Vision on Good and Evil in Michael Schmidt-Salomon - Napierała, Piotr (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
This article is on Michael Schmidt-Salomon’s ethical thought as well as intelectual traditions on which he refers explicitly or could be joined with. Schmidt-Salomon is against of considering good and evil as a scientific or intelectual categories. He claims that there are only good or bad consequences of human actions what exist, so it is impossible to choose and  and represent good or evil, at most one can make a reasonalbe decisions.